Intellectual property rights in China politics of piracy, trade and protection - Cheung, Gordon C. K. (Routledge contemporary China series, 2009)
This book uses the case of intellectual property rights in China to examine how and to what extent market forces and knowledge development affect the relationship between China and the rest of the world.